Cholesterol modulates Orai1 channel function - Derler, Isabella; Jardin, Isaac; Stathopulos, Peter B; Muik, Martin; Fahrner, Marc; Zayats, Vasilina; Pandey, Saurabh K; Poteser, Michael; Lackner, Barbara; Absolonova, Marketa; Schindl, Rainer; Groschner, Klaus; et al. (Science signaling, 2016)
STIM1 (stromal interaction molecule 1) and Orai proteins are the essential components of Ca(2+) release-activated Ca(2+) (CRAC) channels. We focused on the role of cholesterol in the regulation of STIM1-mediated Orai1 currents. Chemically induced cholesterol depletion enhanced store-operated Ca(2+) entry (SOCE) and Orai1 currents. Furthermore, cholesterol depletion in mucosal-type mast cells augmented endogenous CRAC currents, which were associated with increased degranulation, a process that requires calcium influx. Single point mutations in the Orai1 amino terminus that would be expected to abolish cholesterol binding enhanced SOCE to a similar extent as did cholesterol depletion. The increase in Orai1 activity in cells expressing these cholesterol-binding-deficient mutants occurred without affecting the amount in the plasma membrane or the coupling of STIM1 to Orai1. We detected cholesterol binding to an Orai1 amino-terminal fragment in vitro and to full-length Orai1 in cells. Thus, our data showed that Orai1 senses the amount of cholesterol in the plasma membrane and that the interaction of Orai1 with cholesterol inhibits its activity, thereby limiting SOCE.
Keywords: mutace; mastocyty; cholesterol; Mast Cells; buněčné linie; Biotinylation; Protein Structure, Tertiary; cholesterol oxidasa; HEK293 Cells; Cholesterol Oxidase; vápníkové kanály; terciární struktura proteinů; lidé; Histamine; biotinylace; signální transdukce; Calcium Channels; protein ORAI1; vápník; Mutation; fluorescenční spektrometrie; Signal Transduction; HEK293 buňky; Cell Line; Cholesterol; ORAI1 Protein; peptidy; histamin; Calcium; elektrofyziologické jevy; Circular Dichroism; Point Mutation; bodová mutace; Fluorescence Resonance Energy Transfer; Electrophysiological Phenomena; buněčná membrána; Spectrometry, Fluorescence; rezonanční přenos fluorescenční energie; cirkulární dichroismus; Peptides; Cell Membrane; Humans